Safety and efficacy of remimazolam for general anesthesia in elderly patients undergoing laparoscopic cholecystectomy: a randomized controlled trial - So, Keum Young; Park, Jihwan; Kim, Sang Hun (Frontiers in Medicine, 2023)
Introduction There is insufficient evidence regarding the efficacy and safety of remimazolam in elderly patients. Therefore, this study evaluated the differences in the anesthesia characteristics and perioperative hemodynamic profiles of elderly patients receiving total intravenous anesthesia with remimazolam or propofol. Methods Eighty-four patients aged >65 years with an American Society of Anesthesiologists physical status of I–III were randomly assigned to Group R (receiving remimazolam, n = 42) or Group P (receiving propofol, n = 42). In Group R, remimazolam was initiated at a rate of 6 mg/kg/h until loss of consciousness (LOC) was achieved and maintained at 1 mg/kg/h subsequently. In Group P, 1.0–1.5 mg/kg of propofol was injected for 1 min and maintained at 100 μg/kg/min subsequently. The maintenance infusion rate was adjusted to maintain an appropriate depth of anesthesia until the end of the surgery. The primary outcome was the time to LOC. The depth of anesthesia scores and hemodynamic profiles were recorded perioperatively. Results The time to LOC was significantly longer in Group R (120 s) than in Group P (60 s) (p < 0.001). The time to eye-opening (Group R, 10 min; Group P, 10 min; p = 0.056), the incidence of maintenance of hemodynamic changes within 20% of the peri-anesthetic values, and treatments for hemodynamic instability did not differ significantly between the groups. The depth of anesthesia scores did not differ significantly between the groups; however, the scores were higher in Group R than those in Group P before endotracheal intubation. The hemodynamic parameters did not differ significantly at any time point. The time to extubation was longer in Group R (12 min) than that in Group P (10 min) (p = 0.007). Similarly, the time to discharge from the operating room was significantly longer in Group R (15 min) compared to Group P (12 min) (p = 0.018). Conclusion Remimazolam does not exhibit a comparable effect to propofol in terms of anesthesia induction and recovery. However, it demonstrates a similar effect to propofol regarding intraoperative anesthesia depth and hemodynamic profile in elderly patients undergoing remifentanil-based total intravenous anesthesia.